Effect of dose and source of copper supplementation on antioxidant status, humoral immune response and carcass characteristics of lambs - Nagalakshmi, D; Gururaj, K; Senthilkumar, P (The Indian Journal of Animal Sciences, 2011)
An experiment was conducted on 30 male Nellore lambs with average body weight (15.45±0.06 kg) to determine the level of the copper (Cu) supplementation in diet from inorganic and organic sources for higher immunity, carcass production and antioxidant activity by allotting them randomly to 5 groups in completely randomized design. The dietary treatments were, viz. basal diet (BD, no supplemental Cu), BD supplemented with 7 ppm Cu as copper sulphate (CuSO4) and Cu proteinate, and BD supplemented with 14 ppm Cu from CuSO4 and Cu proteinate. The lambs were fed the respective diet at 3.5% of body weight to meet the ICAR requirements except Cu throughout the feeding trial of 180 days. The BD (DM basis) contained 7.38 ppm Cu. The oxidative enzymes i.e. lipid peroxidase (LPx), RBC catalase, RBC superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) activity were estimated at 90 days of feeding trial and the lambs were sensitized with Brucella abortus antigen at 90th day to estimate humoral immune response on 0, 7, 14, 21, 28 and 35 days of post sensitization. At the end of 180 days feeding, 4 lambs from each treatment were slaughtered to study the carcass characteristics. The LPx activity was lower in Cu supplemented lambs and the RBC SOD and catalase activities were higher in Cu-proteinate supplemented lambs at both levels. The antibody titres were higher on 14 ppm Cu supplemented lambs compared to BD lambs. No effect of Cu supplementation was observed on carcass characteristics. This result indicated that supplementation of 14 ppm Cu to a basal diet containing 7.38 ppm Cu increased the oxidative enzyme activities and humoral immune response while Cu supplementation did not influence the carcass traits.